Intenção de escolha de ensino superior privado à luz da Teoria do Comportamento Planejado. - Souza, Ronei Rocha Barreto de (2009)
The aim of the study was to analyze the behavior purchase of the high school students by Planed Behavior Theory (PBT) and their relationship with marketing actions in social choice study in a private college. When behavior consumer investigation is performed, the researchers had highlighted the attitude evaluation by PBT. This kind of theory was developed to explain the intention to perform a behavior based on little set of explanatory constructions - attitude, subjective NORMA, perceived control. The methodology was followed by the instruction proposed by Azen (1991). A qualitative research was performed with 219 high school subjects in two private schools, in Barreiras city, state of Bahia. Descriptive statistics was used (frequency, percentage, mean and standard deviation) to characterize the sample and factorial analysis and confirmatory analysis. The SPSS (version 15.0) and AMOS (version 7.0) were used to data analysis. The family (subjective norm) is decisive to choice intention in college studies and the family considerer the college study a job security in the future. The college infrastructure and the courses offered are important in perception control. It is important that the college keeps projects to the community as traveling library, legal nucleus, nursing and physical therapy clinic (behavior intention). In conclusion, it is expected that the objectives of this dissertation have been achieved. It is showed a contribution to administration field, specially in marketing and social psychology, and the action theories that try to understand consumer behavior.